2014
DOI: 10.2106/jbjs.m.00058
|View full text |Cite
|
Sign up to set email alerts
|

Adult Human Mesenchymal Stem Cells Delivered via Intra-Articular Injection to the Knee Following Partial Medial Meniscectomy

Abstract: There was evidence of meniscus regeneration and improvement in knee pain following treatment with allogeneic human mesenchymal stem cells. These results support the study of human mesenchymal stem cells for the apparent knee-tissue regeneration and protective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
285
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(297 citation statements)
references
References 17 publications
7
285
2
3
Order By: Relevance
“…Our study differs from other research developed in [24][25][26][27][28][29] In humans, other studies have been performed using stem cells from different collection sites such as adipose tissue [30][31][32][33] or peripheral blood through apheresis. 34,35 Some studies include case series and clinical trials with BM mesenchymal cells; some of them administered the cells by means of surgical intervention 13,[36][37][38] and others with intra-articular injection. 12,[39][40][41][42] We evaluated our results by means of VAS and WOMAC scales, since these have been used in many other knee OA studies, 40 in order to determine knee function and pain, and found that there was an improvement from the first week in the BM-SC group.…”
Section: Discussionmentioning
confidence: 99%
“…Our study differs from other research developed in [24][25][26][27][28][29] In humans, other studies have been performed using stem cells from different collection sites such as adipose tissue [30][31][32][33] or peripheral blood through apheresis. 34,35 Some studies include case series and clinical trials with BM mesenchymal cells; some of them administered the cells by means of surgical intervention 13,[36][37][38] and others with intra-articular injection. 12,[39][40][41][42] We evaluated our results by means of VAS and WOMAC scales, since these have been used in many other knee OA studies, 40 in order to determine knee function and pain, and found that there was an improvement from the first week in the BM-SC group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Vangsness et al 18 reported on a randomized double-blind controlled study investigating the safety of intra-articular injection of human mesenchymal stem cells (MSCs) into the knee, the ability of MSCs to promote meniscus regeneration after partial meniscectomy, and the effects of MSCs on osteoarthritic changes in the knee. A total of 55 patients at 7 institutions underwent partial medial meniscectomy.…”
Section: Clinical Studies 2009 To 2014mentioning
confidence: 99%
“…[28][29][30] Furthermore, treatment of patients undergoing partial meniscectomy surgery with an intra-articular injection of allogeneic MSCs has resulted in meniscal regeneration as well as a significant reduction in pain. 31 To achieve successful regeneration with tissue engineering approaches in an osteoarthritic joint, an in-depth understanding is required of how OA-associated inflammation impacts chondrocyte and progenitor cell behavior. Addressing inflammatory processes in OA with TERM strategies may not only facilitate successful repair but halt the progressive destruction of an OA joint.…”
Section: -24mentioning
confidence: 99%